Effect of soiling and sunlight exposure on the performance ratio of photovoltaic technologies in Santiago, Chile. (15th April 2016) - Urrejola, Elias; Antonanzas, Javier; Ayala, Paulo; Salgado, Marcelo; Ramírez-Sagner, Gonzalo; Cortés, Cristian; Pino, Alan; Escobar, Rodrigo
Highlights: Performance ratio of PV panels decays daily between 0.13% and 0.56% under soiling. PV panel degradation is 1.29% for poly, 1.74% for mono and 2.77% for thin film. An annual weather-corrected performance ratio of 75% is calculated. A critical cleaning period of 45 days is proposed, no matter cleaning and energy prices. Abstract: The performance, yearly degradation, and annual yield of photovoltaic systems have been studied in outdoor exposure for two years period 2014–2015 in Santiago, capital of Chile. Photovoltaic panels performance degrades daily in a rate between −0.13% and −0.56% under soiling in highly polluted Santiago, Chile. Yearly degradation of the arrays system was found to be in the order of 1.29% for the polycrystalline array, 1.74% for the monocrystalline array, and 2.77% for the thin film system array. The annual production yield reached 1419–1373 kW h/kWp for Poly, 1459–1444 kW h/kWp for Mono, and 1248–1236 kW h/kWp for TF, in 2014 and 2015, respectively. The annual in-plane irradiation measured reached 1981.3 kW h/m 2 and 1943.2 kW h/m 2, for 2014 and 2015, respectively. A weather-corrected performance ratio is presented showing a yearly performance ratio of around 75% for all technologies. Monthly cleaning and random rain fall have shown positive effects as primarily solutions. Furthermore, we studied the optimal strategies of cleaning for different energy prices and we defined a critical cleaning period of 45 days for a real case, independent on cleaning cost and energy prices. This work contains novel results for the Chilean capital city and can be applied to future installations in the area and serve as further insights for the development of solar energy in Chile.